CP-077 Evolution of the off-label use of bevacizumab in oncology patients. (25th February 2017) - Pozo, JF Marin; Rovira, P Sanchez; Perez, JM Duarte; Almazan, M Merino; Ruiz, A Sanchez; Porras, I Caba; Lopez, A
Abstract : Background: Bevacizumab is a very expensive antineoplastic drug that since its commercialisation has been used in an increasing number of indications. Different studies have shown a high percentage of off-label use of this drug. Purpose: This work analyses the evolution and reasons for off-label use of bevacizumab at two different cut-off dates (2012, 2016) in the oncology unit of a regional hospital. Material and methods: An observational study of the post-marketing use of drugs was undertaken. Data collected were diagnosis, line treatment, associated drugs and doses of bevacizumab prescribed to cancer patients from January to August 2016. The technical label (TL) updated in 2016 was used to determine the frequency of off-label use. These data were compared with the results obtained in the MAR-BEV-2013-01 study (data obtained from patients in 2012). Results: The total number of prescriptions for bevacizumab was 39, which corresponded to 37 patients. The diagnoses associated with use were 20 metastatic colorectal cancers, 6 metastatic breast cancers (mBC), 5 cervical cancers, recurrent or metastatic (mCC), 3 glioblastomas (GLB), 2 ovarian cancers, 2 non-small cell lung cancers and one hepatocellular carcinoma (HPC). The frequency of off-label use was 12.8% (5 requirements). The reasons for non-compliance with the TL were 4 prescriptions (10.2%) by diagnosis (3 GLB and 1 HPC) and 1 (2.6%) prescription by line (secondline of mBC). These results are markedly lower than those obtained in the MAR-BEV-2013-01 study: 42.9% off-label use (14.6% by diagnosis, 15% by line and 12.5% by associated drug). If we apply the criteria of 2012 for off-label use to prescriptions in 2016, the result is 25.6% off-label use. There was a significant decline that is more meaningful if it takes into account the 5 prescriptions for mCC that would not be off-label use if the indication had been adopted in 2012. Conclusion: The use of bevacizumab in conditions different from those contained in the TL has decreased significantly in our health area. This decrease was motivated by a change in the criteria for the prescription and not by the modification of the TL of the drug, which may also contribute to more efficient use of bevacizumab. No conflict of interest